PENERAPAN ALGORITMA SIMPLE ADDITIVE WEIGTHING MENENTUKAN LAHAN PERTANIAN UNTUK BUDIDAYA TANAMAN CABAI - Berna, Aldera; Lelah, Lelah (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
Chili plants are one of the most popular agricultural products. Sometimes, the price may go up several times, other times it will fall sharply. Since prices often go up several times, many farmers want to plant in large quantities. Pepper farmers also often face obstacles, one of which is the determination of land to plant chilies, because the yield of chili plants depends on the quality of the soil used. The existence of a “decision support system to identify chili plants” can help farmers make decisions through good planning before doing anything on their land. The presence of a Chilli Plant Determination Decision Support System with the Simple Additive Weight Method can also facilitate the dissemination of information and knowledge through applications that can be accessed at any time. This application is made using the PHP programming language and MySQL as the database.